The Language Production Strategy by the Indonesian Government: A Crucial Effort to Prevent Social Disorders and Control Community Behavior During the Covid-19 Pandemic, Analyzed through Roger Fowler's Critical Discourse Analysis - Ekaristianto, Felix Brian Hari; Sulistyowati, Ririn (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2024)
Coronavirus disease (COVID-19) is a virus that causes a global pandemic. The World Health Organization (WHO) has declared the COVID-19 pandemic since March 11, 2020. During the pandemic, the Government needs to make efforts to prevent social disturbances from occurring, so control over people's behavior needs to be carried out. One of the efforts to control people's behavior carried out by the Indonesian Government is to produce language forms. This form of language is still used today, even though the pandemic has passed. This research will discuss these forms of language using Roger Fowler's Critical Discourse Analysis theory. The data used in this research was obtained from secondary sources from previous research regarding the lexicon that emerged during the COVID-19 pandemic. The secondary data was classified based on its forms; then, an in-depth analysis was carried out using Roger Fowler's Critical Discourse Analysis theory. After the analysis is carried out, conclusions are drawn inductively. The results of this research show that the Government uses several forms of language to prevent social disturbances and control the behavior of Indonesian society. These forms are abbreviations, acronyms, words, and phrases. These forms are used to prevent and overcome social disturbances that arise in Indonesian society in facing the COVID-19 pandemic.